Determinants of Customer's Equity: An Empirical Studies on BPRS Customers in Ex Banyumas Residency Central Java - Muksin, Abdullah; Ruwaida, Ruwaida; Arifin, Zainal; Madyanti, Aniza Nur; Safri, Safri (International Review of Management and Marketing, 2018)
The purpose of this paper is to find and analyze the determinants that significantly BPRS Customers Equity in ex. Banyumas residency, Central Java. Problems of this research formulated in 7 hypotheses that SEM tests analysis with Lisrel 8.80 shoves ware and 335 respondents. Test results hypothesis by using the descriptive and verified analysis. There is the influence positive and significances the customer Trust, and Satisfaction together to customers loyalty with impacts contributions(R2) 0,66 and F-account 12,50, and there is the influence positive and significances the customer Trust, Satisfaction, and customer loyalty variables together to customers equity with impacts contributions(R2) 0,84 and F-account 12,30, wherever customers loyalty is dominant variable to more influence for customer equity, than customer loyalty as full mediating variables for customers trust and customer satisfaction to BPRS customers equity in ex. Banyumass residency central Java. Advice managerial, to build customers equity, in the future, Management BPRS have to build customers loyalty trough the customers relation management. While to improve customer's loyalty, management BPRS have to build customers trust, and customer satisfactions trough the promotion and education about sharia banking to BPRS customers ex. Banyumass residency central Java. Keywords: Customer Trust, Customer Satisfaction, Customer Loyalty and Customer Equity. JEL Classifications: M30, M31